2003
DOI: 10.2139/ssrn.482648
|View full text |Cite
|
Sign up to set email alerts
|

Top Management Turnover: An Analysis of Active Australian Investment Managers

Abstract: Abstract:This study examines the relationship between top management turnover (i.e. investment directors) and investment performance for actively managed Australian funds. This issue is significant given the importance of executive management in the implementation of the institution's investment strategy, the sizeable assets under their control, as well as the overall success and profitability of the funds management operation. In addition, investors, asset consultants, managed fund ratings agencies and the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
(45 reference statements)
2
12
1
Order By: Relevance
“…To facilitate further tests on this issue, we define a voluntary departure as a manager leaving the company when the fund they manage has obtained positive objective adjusted returns in the year before their departure. This is consistent with the definition of forced departure used in both Khorana (2001) and Gallagher and Nadarajah (2004).…”
Section: Manager Resignation and Retirementsupporting
confidence: 87%
See 2 more Smart Citations
“…To facilitate further tests on this issue, we define a voluntary departure as a manager leaving the company when the fund they manage has obtained positive objective adjusted returns in the year before their departure. This is consistent with the definition of forced departure used in both Khorana (2001) and Gallagher and Nadarajah (2004).…”
Section: Manager Resignation and Retirementsupporting
confidence: 87%
“…Khorana, 1996;Gallagher, 2003;Gallagher and Nadarajah, 2004). The studies generally find an inverse relation between the probability of managerial replacement and fund performance and, therefore, conclude that control mechanisms within fund companies are effective.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, contrary to Khorana's conclusions, they claimed that a change of fund managers does not improve the performance of funds, where earlier inefficient managers were employed, nor does it deteriorate the performance of funds, where earlier decisions were taken by efficient managers. Gallagher and Nadarajah (2004) found that managerial replacement in Australian equity, fixed income and balanced funds (in the period 1991-2001) resulted in the reversal of performance both for underperformers and outperformers (they used such measures as objective-adjusted return, one-factor alpha and four-factor alpha (only for equity funds)). These conclusions were consistent with Khorana. In the years 1997-2011 Clare, Motson, Sapuric and Todorovic (2014) carried out an analysis of changes of portfolio managers in the UK.…”
Section: Changes Of Portfolio Managers -A Review Of the Selected Studiesmentioning
confidence: 99%
“…For example, it is believed that, fund scale increases at the cost of reducing liquidity and increasing administrative expenses, which may result in worse fund performance [2,13,16]; on the contrary, positive impacts, such as economic of scale, are also identified in the mutual fund market [18]. Interestingly, there is also a line of literature claiming no significant correlations [1,12,5,9]. Besides, some researchers have proposed a thresholdbased structure: The cost corresponding to a larger fund scale may increase dramatically only when it is beyond a threshold [22,14,4], such that the performance is associated with the scale via an inverse-U relationship.…”
Section: Introductionmentioning
confidence: 99%